Cardiac mitochondrial bioenergetics, oxidative stress, and aging - Judge, Sharon; Leeuwenburgh, Christiaan (American Journal of Physiology: Cell Physiology, 2007)
Mitochondria have been a central focus of several theories of aging as a result of their critical role in bioenergetics, oxidant production, and regulation of cell death. A decline in cardiac mitochondrial function coupled with the accumulation of oxidative damage to macromolecules may be causal to the decline in cardiac performance with age. In contrast, regular physical activity and lifelong caloric restriction can prevent oxidative stress, delay the onset of morbidity, increase life span, and reduce the risk of developing several pathological conditions. The health benefits of life long exercise and caloric restriction may be, at least partially, due to a reduction in the chronic amount of mitochondrial oxidant production. In addition, the available data suggest that chronic exercise may serve to enhance antioxidant enzyme activities, and augment certain repair/removal pathways, thereby reducing the amount of oxidative tissue damage. However, the characterization of age-related changes to cardiac mitochondria has been complicated by the fact that two distinct populations of mitochondria exist in the myocardium: subsarcolemmal mitochondria and interfibrillar mitochondria. Several studies now suggest the importance of studying both mitochondrial populations when attempting to elucidate the contribution of mitochondrial dysfunction to myocardial aging. The role that mitochondrial dysfunction and oxidative stress play in contributing to cardiac aging will be discussed along with the use of lifelong exercise and calorie restriction as countermeasures to aging.